Science Teachers' Perceptions The Merdeka Curriculum Implementation In Entikong Border State Junior High Schools - Kusudaryani, Praditya Adi; Hairida, Hairida; Masriani, Masriani (Universitas Pendidikan Mandalika, 2024)
Merdeka Curriculum emphasises the implementation of differentiated learning and considers the unique characteristics of each student. Teachers have an important role in the development and implementation of this curriculum, and must have interpretations in accordance with the provisions of curriculum development. Teachers' perceptions of the Merdeka Curriculum are very diverse and can significantly affect the readiness and quality of learning to be carried out. This study aims to determine teacher perceptions based on aspects of cognition, affection, conation. This research uses a qualitative descriptive method with data collection techniques using questionnaires, in-depth interviews, and documentation. The research questionnaire used is an open question that has been validated for content by 3 Merdeka Curriculum experts and validated for items by Merdeka Curriculum experts and Educational Psychology Experts. The results showed that teachers' perceptions are very important in implementing the Merdeka Curriculum, cognition about general concepts is positive, but for in-depth concepts, teachers' perceptions are negative. Schools that provide gradual training have succeeded in building teachers' positive cognition, although many still think that teaching modules are the same as lesson plans from the 2013 Curriculum. Teachers support the development of Merdeka Curriculum even though they feel there are limitations in understanding and readiness of infrastructure in schools. Teachers are also positive about the support and cooperation between teachers, especially through MGMP, but still feel that they are not fully capable of making their own learning tools. Although the teaching modules are in accordance with the provisions, teachers have not fully implemented differentiation plans or utilised the results of learning style diagnosis in learning.